TOWARDS A RATIONAL USER FEE SYSTEM FOR TOURISM IN SAGADA, PHILIPPINES - ABANSI, CORAZON L. (ITB Journal Publisher, LPPM ITB, 2012)
The study attempts to analyze the potential of developing a user fee system for the sustainable development of tourism in Sagada, Mountain Province, Philippines. Estimates of willingness to pay of tourists for nature’s services derived from a nonmarket valuation study provided the springboard for the range of user fees. Use allocation of potential revenue from user fee included education and awareness, improvement of facilities, waste minimization and clean-up, capacity building, and response to accidents and disasters. A council composed of various stakeholders was identified to be the institutional mechanism for developing, adopting and evaluating the operational policies as well as reviewing and approving programs and projects to be financed by the fund. Policy procedures and processes including information sharing and consultation, and the administrative arrangements for implementation and enforcement would best be conducted through this management authority to ensure that the environment and the community benefit the most.